Tissue distribution of cells derived from the area opaca in heterospecific quail-chick blastodermal chimeras - Karagenç, Levent (Blackwell Science Inc, 2010)
The objective of the current study was to determine the tissue distribution of cells derived from the area opaca in heterospecific quail-chick blastodermal chimeras. Quail-chick chimeras were constructed by transferring dissociated cells from the area opaca of the stage X–XII (EG&K) quail embryo into the subgerminal cavity of the unincubated chick blastoderm. The distribution of quail cells in embryonic as well as extra-embryonic tissues of the recipient embryo were examined using the QCPN monoclonal antibody after 6 days of incubation in serial sections taken at 100-μm intervals. Data gathered in the present study demonstrated that, when introduced into the subgerminal cavity of a recipient embryo, cells of the area opaca are able to populate not only extra-embryonic structures such as the amnion and the yolk sac, but also various embryonic tissues derived from the ectoderm and less frequently the mesoderm. Ectodermal chimerism was confined mainly to the head region and was observed in tissues derived from the neural ectoderm and the surface ectoderm, including the optic cup, diencephalon and lens. Although the possibility of random incorporation of transplanted cells into these embryonic structures cannot be excluded, these results would suggest that area opaca, a peripheral ring of cells in the avian embryo destined to form the extra-embryonic ectoderm and endoderm of the yolk sac, might harbor cells that have the potential to give rise to various cell types in the recipient chick embryo, including those derived from the surface ectoderm and neural ectoderm.